Development of a Risk Control System for the Granulation Process of Ferronickel Skimming Slag Based on HAZOP Analysis Results - Hendri Saputro; Rochim Bakti Cahyono (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Occupational safety in mining and metallurgical operations continues to be a major concern because these processes involve extreme temperatures, hazardous materials, and complex interactions between workers and equipment, especially in ferronickel smelting where slag handling occurs under high thermal and pressure conditions. Objective: This study aims to develop and validate an integrated risk control system for the ferronickel slag skimming granulation process based on Hazard and Operability Study analysis. Method: A descriptive qualitative-quantitative case study approach was applied by analyzing three main process nodes using Hazard and Operability Study worksheets, supported by a 5×5 risk matrix to evaluate initial and residual risks, followed by the design and validation of engineering and administrative control systems. Result and Discussion: The slag granulation process was identified as a high-risk operation with several critical deviations, where Low Pressure Water showed the highest initial risk value (16) due to its potential to trigger failed granulation, slag agglomeration, and explosions. The main influencing variables included water jet pressure, slag temperature, water flow rate, pump condition, drill gun performance, and nozzle blockage. The developed risk control system integrated engineering and administrative controls, resulting in consistent risk reduction across all process nodes. Conclusions: Hazard and Operability Study-based risk control system effectively reduces process risk with an effectiveness range of 40%-75% and an average reduction of 56.62%, enhances process reliability, strengthens process safety management, and supports the development of a proactive safety culture in ferronickel smelter operations